Disease Dynamics in Hard Corals: Transmission Study of Desulfovib-rio salexigens and Acinetobacter sp - Rahmi; Jompa, Jamaluddin; Khairun Nisaa; Akmal (Department of Aquaculture, 2025)
The objective of this study was to analyze the dynamics of spread and tissue damage due to infection with Black Band Disease (BBD) on Pachyseris sp. and Brown Disease (BrB) on Acropora sp. Additionally, the effect of ambient temperature on transmission rates was investigated. The results demonstrated that BBD on Pachyseris sp. caused progressive tissue damage, characterized by zones of necrosis and distinctive black bands separating healthy tissue from dead tissue. At 31°C, the disease transmission rate increased twofold compared to 29°C, with an infection rate reaching 1.72 ± 0.76 cm/day. BrB on Acropora sp. showed the highest infection rate reaching 2.20 ± 0.41 cm/day at 29°C with a bacterial concentration of 106 CFU/ml. However, the infection rate decreased significantly at 31°C for all bacterial concentrations tested. The disease propagated linearly along the coral branches, manifesting as yellowish-brown discolouration attributable to symbiont ciliate activity. The virulence of pathogens such as Acinetobacter sp. increased at 31°C, accelerating the spread of necrosis through the production of toxins and enzymes that damage the coral epithelium. BrB symptoms appeared within 2 days at 29°C and only 1 day at 31°C. This study confirms that high temperature and sedimentation play a key role in accelerating disease dynamics in corals. Increasing seawater temperatures due to global climate change create ideal conditions for the spread of disease, threatening the sustainability of coral reef ecosystems. To mitigate these challenges, a multifaceted approach involving environmental management, carbon emission reduction, and the development of biotechnology to enhance coral resistance to pathogens is essential.